2022
DOI: 10.3390/ijerph19095335
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Medication Use among Pregnant and Postpartum Women during the Third Wave of the COVID-19 Pandemic: A European Multinational Cross-Sectional Study

Abstract: Information on medication utilization among pregnant and postpartum women during the pandemic is lacking. We described the prevalence and patterns of self-reported medication use among pregnant and postpartum women during the third wave of the pandemic (June–August 2021). An online questionnaire was distributed in five European countries between June–August 2021. Pregnant women or women who had delivered in the three preceding months, and ≥18 years old, could participate. The prevalence of overall medication u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
14
1
Order By: Relevance
“…Specific groups of medicines for which HCPs want information were identified, including systemic anti-infectives and respiratory and alimentary tract medicines. These medicines are also regularly used in this population [ 30 , 31 , 32 , 33 , 34 , 35 ]. Moreover, women and HCPs expressed their interest in having access to information on herbal remedies.…”
Section: Discussionmentioning
confidence: 99%
“…Specific groups of medicines for which HCPs want information were identified, including systemic anti-infectives and respiratory and alimentary tract medicines. These medicines are also regularly used in this population [ 30 , 31 , 32 , 33 , 34 , 35 ]. Moreover, women and HCPs expressed their interest in having access to information on herbal remedies.…”
Section: Discussionmentioning
confidence: 99%
“… Overview on the different themes and specific papers discussed in this Special Issue [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. …”
Section: Figurementioning
confidence: 99%
“…As the migratory phenomenon represents a structural element of society, it is hereby reassuring that the prescription patterns only showed minor differences between both groups, while inappropriate prescription (antihypertensives, statins, anti-inflammatory drugs) was limited in both groups [ 13 ]. Two other papers focused on another ‘intercurrent’ event (the COVID-19 pandemic) and its effects on medicines utilization in pregnant and breastfeeding women in different European countries [ 14 , 15 ]. Both studies hereby used a self-reported approach of the end users.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Vitiello et al stated that “some oral analgesic drugs used for self-medication can be used in pregnancy, such as ibuprofen, which has been shown to be safe for pregnant patients with covid-19” and referred to our manuscript. However, our manuscript and follow-up publication ( Gerbier et al, 2022 ) present the results of drug utilization studies and only provide prevalence estimates on the perinatal use of the non-steroidal inflammatory drug (NSAID) ibuprofen during the COVID period (<1% in pregnancy). Such studies neither aim to provide evidence of safety, nor obtain insight into specific risks associated with the use of ibuprofen or NSAIDs in pregnancy.…”
mentioning
confidence: 99%